KETERAMPILAN PEMBUATAN PRODUK PRAKARYA MELALUI MODEL BLENDED LEARNING BERBASIS TELEGRAM PADA MASA PEMBELAJARAN TATAP MUKA TERBATAS - Vriska Tarlia Nalar (Journal of Chemistry Education and Integration, 2023)
This Limited Face-to-Face Learning Process (PTMT) is carried out by reducing the number of students in the class and reducing the allocation of learning time at each meeting for students, for example in chemistry subjects which were originally 3 x 45 minutes now to 1 x 45 minutes in one week , in the craft subject, which was originally 2 x 45 minutes now becomes 1 x 45 minutes in one week. The limited time allotted for face-to-face meetings, the researchers used the Telegram-free Blended Learning Model, the learning process was carried out in collaboration between Chemistry and Craft subjects in Improving Students' Skills in Making a Product that Has Selling Value During the Limited Face-to-Face Learning Period (PTMT) in Class X MIPA 3 SMA Negeri 3 Kundur, where the results of this research students can make a product that has a selling value, namely making hand sanitizer.Keywords : Blended Learning Model, Telegram, Limited Face-to-Face Learning